Revision of the genus Glyptoxanthus A. Milne-Edwards, 1879, and establishment of Glyptoxanthinae nov. subfam. (Crustacea: Decapoda: Brachyura: Xanthidae) - Mendoza, Jose Christopher E.; Guinot, Danièle (Zootaxa, 2011)
The xanthid genus Glyptoxanthus A. Milne-Edwards, 1879, known from the tropical eastern Pacific, western and eastern Atlantic, and the Red Sea, is revised as part of an ongoing revision of the subfamily Euxanthinae Alcock, 1898. Analysis of morphological characters shows that Glyptoxanthus must be excluded from the subfamily Euxanthinae and placed in a distinct subfamily, Glyptoxanthinae nov. subfam. The new subfamily has affinities to Euxanthinae, Actaeinae Alcock, 1898, and Zalasiinae Serène, 1968, but it is distinguished from these by a suite of characters in the thoracic sternum, third maxillipeds, epistome, chelipeds, and male abdomen and gonopods. All the included species are re-diagnosed, with additional comments and updates on their biology and distribution. In an effort to stabilize the taxonomy of the genus and some of its species, neotypes were selected for G. erosus (Stimpson, 1859) (type species), G. labyrinthicus (Stimpson, 1860), and G. meandricus (Lockington, 1877). A key to the genus is included.